Measuring water retention in undisturbed samples of stony soils - Caroline Andrade Pereira; Rodrigo Pivoto Mulazzani; Quirijn de Jong Van Lier; Fabrício de Araújo Pedron; Paulo Ivonir Gubiani (Scientia Agricola, 2023)
ABSTRACT Stony soils have been increasingly used for agriculture production; however, little is known about their hydraulic properties due to problems, such as sample deformation and hydraulic continuity between samples and suction devices when the sampling and measurements are accomplished with traditional techniques. In this study, the traditional ring sampling technique was replaced by the sampling of undisturbed soil blocks coated with paraffin wax to preserve their structure. A saturated paste of fine-grained mineral particles was used to ensure contact and hydraulic continuity between samples and suction devices (sand table and ceramic plates). This allowed us to determine 30 water retention curves for three stony soils with coarse particle contents (> 2 mm) ranging from zero to 69 %. The van Genuchten model was fitted to the measured retention data and the root mean square errors were between 0.0034 and 0.0331 m3 m–3, with no outliers or odd behavior in the retention curves. These results showed that consistent water retention curves for stony soils can be determined with the technique proposed. Fine-grained minerals sandwiched between the surface of suctions sources and sampled blocks improve hydraulic continuity between them. These techniques can be applied to determine water retention properties in structured soil samples with coarse particles where it is unfeasible to collect structured soil samples with metal sampling rings.